Educational Semantics Deduced from some Jurisprudential Rules (Journal Of Educational and Psychological Researches, 2024)
This research aims to identify the educational, devotional, and moral connotations of some jurisprudential rules. To achieve this goal, the research used the descriptive approach according to the deductive approach. Six jurisprudential rules have been identified to derive these connotations: the rule of "warding off evil ahead of bringing interests,"  the rule of "harm is still like it,"  the rule of "the realization of speech is the first of neglect," and the rule of "the installer is ahead of the negative."  The rule of "forgivable in the means of what is unforgivable in the purposes" and the rule of "hastened the thing before its time punished by depriving it" The research found that the most important of them are: Islamic education is based on the sources of legislation and distinguishes its characteristics and the diversity of its methods, as the research revealed the educational connotations of devotional in some jurisprudential rules, including submission to the orders of God, charity, patience, and keeping the tongue. Then, revealing the moral educational connotations in some jurisprudential rules, most notably: the significance of conviction, the significance of identification and verification, and the significance of honesty.